Discontinuation of biosimilar infliximab in Japanese patients with rheumatoid arthritis achieving sustained clinical remission or low disease activity during the IFX-SIRIUS STUDY I (the IFX-SIRIUS STUDY II): Study protocol for an interventional, multicenter, open-label, single-arm clinical trial with clinical, ultrasound and biomarker assessments. Issue 32 (7th August 2020) - Shimizu, Toshimasa; Kawashiri, Shin-Ya; Sato, Shuntaro; Morimoto, Shimpei; Minoda, Shuri; Kawazoe, Yurika; Kuroda, Shohei; Tashiro, Shigeki; Sumiyoshi, Remi; Hosogaya, Naoki; Yamamoto, Hiroshi; Kawakami, Atsushi
Abstract: Background: The introduction of biological disease-modifying anti-rheumatic drugs into clinical practice has dramatically improved the clinical outcomes of individuals with rheumatoid arthritis (RA). We are conducting the IFX-SIRIUS STUDY I that evaluates whether switching from originator infliximab (IFX) to its biosimilar, CT-P13, is not inferior in maintaining nonclinical relapse to continue treatment with originator IFX in patients with RA achieving clinical remission. It is the next great issue whether disease activity can be maintained in good condition after discontinuation of CT-P13 because no evidence is available regarding the clinical value of discontinuing biosimilars in patients with RA. Thus, we will evaluate whether a condition without clinical relapse will be maintained after discontinuation of CT-P13 in patients with RA, achieving clinical remission or low disease activity during the IFX-SIRIUS STUDY I. Methods/design: This study is an interventional, multicenter, open-label, single-arm clinical trial with a 48-week follow-up. Patients with RA who are treated with CT-P13 and sustained nonclinical relapse during the IFX-SIRIUS STUDY I will be included. Patients will discontinue CT-P13 after the study period of the IFX-SIRIUS STUDY I. We will evaluate disease activity by clinical disease activity indices and musculoskeletal ultrasound (MSUS). The primary endpoint is the proportion of patients who do not have clinical relapse during the study period. Important secondary endpoints are the changes from the baseline of the MSUS scores. We will also comprehensively analyze the serum levels of multiple biomarkers, such as cytokines and chemokines. In addition, if a clinical relapse occurs in patients after the discontinuation of CT-P13, we will evaluate the effectiveness and safety of restarting CT-P13. Discussion: The study results are expected to show the clinical benefit of the discontinuation of CT-P13 and effectiveness and safety of restarting CT-P13 after clinical relapse. The strength of this study is to prospectively evaluate the therapeutic effectiveness by not only clinical disease activity indices but also standardized MSUS findings in multiple centers. We will explore whether parameters at baseline can predict a nonclinical relapse after the discontinuation of CT-P13 by integrating multilateral assessments, that is, patient's characteristics, clinical disease activity indices, MSUS findings, and serum biomarkers. Trial registration: This study was registered in the Japan Registry of Clinical Trials (https://jrct.niph.go.jp ) on April 20, 2020 as jRCTs071200007.